The Disneyization of society - Bryman, Alan (SAGE, 2004)
Arguing that the contemporary world is increasingly converging towards the characteristics of the Disney theme parks, i.e. social environments that are driven by combinations of forms of consumption, this text demonstrates the importance of control and surveillance in consumer culture.